Twenty-five years of income inequality in Britain: The role of wages, household earnings and redistribution - Jonathan Cribb; Robert Joyce; Thomas Wernham (Institute for Fiscal Studies (IFS), 2022)
We study earnings and income inequality in Britain over the 25 years prior to the COVID-19 pandemic. We focus on the middle 90% of the income distribution, within which the gap between top and bottom in 2019-20 was essentially the same as a quarter-century earlier. We show that this apparent stasis is in fact the net effect of various mutually offsetting changes which are important in their own right. The proportion of working-age households with no one in paid work has been falling for most of the period, reducing inequalities in household labour income across the working-age population. Between the mid 1990s and the Great Recession, however, the gap in earnings between low-earning working households and higher-earning working households was rising, due in part to an increasing tendency for low-wage men to work part-time. But increasing fiscal redistribution kept the gap in disposable income between those same households roughly constant, while also closing the gap between the incomes of workless households and the rest. Together with the falls in worklessness, this was sufficient to achieve some decline in income inequality across the middle 90% of the distribution. In the past decade, key trends turned around. Household earnings inequalities reversed direction, as hours of work for low-wage men stopped falling and hourly wage growth was strongly progressive for both men and women - in part due to a rising minimum wage. Yet household disposable income inequalities also reversed, in the opposite direction, due to large cuts to working-age income-related transfers.
Keywords: D31; E24; J3; 330; inequality; labour market; redistribution